Pelatihan Pembuatan Proposal Hibah Kompetitif Untuk Meningkatkan Kualitas Publikasi Mahasiswa di Universitas Muhammadiyah Kalimantan Timur - Aullia Vivi Yulianingrum (CV Putra Publisher, 2023)
One indicator of the quality of Indonesian education is the increase in student publications. Through various competitive grant programs, students are expected to be able to compete for funding from the government and the private sector. Therefore, it is necessary to have training in making proposals that are able to compete in grant competitions that aim to: 1) increase student publications; 2) encourage students to produce quality proposals; 3) produce scientific work that is interesting, innovative so that it can be recognized at the national or international level. The method used is training and assistance in making proposals. The presenters of the resource person training were lecturers with training participants at the Muhammadiyah University of East Kalimantan. The output of this activity is so that students can compete and get research funding and community service. The outcome obtained is to bring student participation closer to society and the role of students as agents of change in the dynamics of today's rapidly developing society.